PENGARUH KEBERAGAMAN TENAGA KERJA TERHADAP KINERJA KARYAWAN YANG DIMODERASI OLEH LINGKUNGAN KERJA NON FISIK - HANUM M, SILSIANI; KISTYANTO, ANANG (Jurnal Ilmu Manajemen (JIM), 2018)
This phenomenon is one of the most challenging human resources in organizational matters. One of the management challenges facing organizations today is adapting to different individuals. We describe this challenge as the diversity of the workforce. The diversity of labor means the difference or equality of each individual in terms of age, gender, caste, experience, professional qualifications and employees coming from different geographical regions. This study aims to analyze the effect of labor diversity on employee performance with non physical work environment as a moderator variable. The sample used in this study amounted to 50 employees, namely all employees of the bureau at Petra Christian University Surabaya. Data analysis technique used is Structural Equation Model Partial Least Square with the help of Smart PLS 3.0 software. The results of this study show that the diversity of labor has a significant effect on employee performance. Employee performance has a significant effect on the work environment. And the work environment weakens the influence of the diversity of labor that has a significant effect on employee performance.